How extra-ordinary public servants shield schools from perpetual underachievement - Modiba, N. S. (International Conference on Public Administration and Development Alternatives (IPADA), 2018)
The paper critically reflects on how the most devoted and conscientious public servants in schools, overturn underperformance into higher academic achievement. The paper is empirical in approach. Interviews and document study were used to collect data from three selected secondary schools in one of the Districts of Limpopo Province. Research findings reveal that, institutional underachievement is a product of inappropriate and inadequate service delivery. Findings showed that, allowing the culture of underperformance to take root, by public schools, becomes an educational albatross enough to dismantle, oppose and to defeat. In addition, findings indicated that, the absence of decolonisation attitude in schools, which revolutionises amounts to emancipation without freedom to institutional incumbents. Lastly, not all educational institutions deserve to first, offer mediocre performance before they revive and enhance their educational service. On the basis of the above, the researcher recommends that public secondary schools need to experiment with the 21st century manner of managing and leading learning institutions where decolonisation of every practice at the school, permeates every corner of a school’s governance and administration. Such a change of focus is likely to assist schools to deinstitutionalise the entrenched colonialism which is irrelevant in the 21st century schooling since it meddles with the delivery of a quality public service by public servants in schools.
Journal article publishes in the 3rd Annual International Conference on Public Administration and Development Alternatives 04 - 06 July 2018, Stellenbosch University, Saldahna Bay, South Africa
Keywords: Conscientious; Deinstitutionalisation; Enhance; Revolutionise; Deinstitutionalization; Underachievement; Civil service; Teachers